Simultaneous estimation of phenylpropanolamine hydrochloride and cetirizine hydrochloride in tablet dosage form by rp-hplc method. - SIPRA SARKAR; KRISHNENDU BASAK (International Journal of Pharma and Bio Sciences, 2018)
In the present study a simple, accurate and precise reverse phase liquid chromatographic method has been developed and validated for simultaneous estimation of Phenylpropanolamine Hydrochloride and Cetirizine Hydrochloride from tablet dosage form as the reversed rhase HPLC method is most suitable for the estimation of both the ingradient simultaneously..The method was developed using Waters HPLC system on L1 column (Hypersil Gold: 250mm x 4.6 mm, 5µm) using a mixture of 0.02 M Sodium dihydrogen orthophosphate solution and Acetonitrile in the ratio 50:50 v/v & 1ml Triethylamine as mobile phase (pH of mobile phase was adjusted to 4.0 with 10% Ortho-phosphoric acid/ Sodium Hydroxide) in an isocratic elution mode at a flow rate of 1.0 ml/min, at 30ºC with a load of 20µl. The detection was carried out at 254 nm. The retention time of Phenylpropanolamine Hydrochloride and Cetirizine Hydrochloride was found to be around 4.1 min and 7.1 min respectively. The method was validated with respect to linearity, robustness, precision and accuracy. The proposed method was successfully applied for the simultaneous quantitative determination of Phenylpropanolamine Hydrochloride and Cetirizine Hydrochloride from the tablet dosage form.